2021
DOI: 10.1021/acs.jafc.1c00741
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Phenols and Alkylamides of Sichuan Pepper (Zanthoxylum Genus) in α-Glucosidase Inhibition: A Structural Mechanism Analysis

Abstract: The phenols and alkylamides in 26 varieties of Zanthoxylum pericarps (ZP) were comparatively identified, and the contribution of these key components to the inhibition of in vitro α-glucosidase (α-Glu) was confirmed using principal component analysis (PCA) and ingredient recombination models. Additionally, spectrophotometric assays, nuclear magnetic resonance (NMR), and molecular docking (MD) were employed to characterize the interactions among key components in ZP when exposed to α-Glu. Four phenols and hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Sichuan pepper has been used as a culinary ingredient and for medicinal purposes since a long time ago, and is an economicallyimportant shrub species (Cao et al, 2021;. Spice produced from Sichuan pepper has a good anti-inflammatory, antimicrobial, and antioxidant activity (Liu et al, 2021;Zhang, Huang, Zhang, et al, 2021;Zhang, Liu, Wei, & Gou, 2021;Zhang, Liu, Yang, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sichuan pepper has been used as a culinary ingredient and for medicinal purposes since a long time ago, and is an economicallyimportant shrub species (Cao et al, 2021;. Spice produced from Sichuan pepper has a good anti-inflammatory, antimicrobial, and antioxidant activity (Liu et al, 2021;Zhang, Huang, Zhang, et al, 2021;Zhang, Liu, Wei, & Gou, 2021;Zhang, Liu, Yang, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Sichuan pepper is used in food and traditional Chinese medicine (Zhang, Huang, Zhang, et al, 2021;Zhang, Liu, Wei, & Gou, 2021;Zhang, Liu, Yang, et al, 2021;Zheng et al, 2021). China's largest Karst valley area is located in the Southwestern region, where soil is shallow, sticky and with low water-holding capacity (Gan, He, & Qin, 2020;Gan, He, Qin, & Li, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As displayed in ▶ Fig. 5 c, the value of maximum velocity V max (the y-intercept) remained the same while Michaelis-Menten constant (K m ) increased with the increasing concentration of ASOPC, indicated that ASOPC is a competitive inhibitor of α-glucosidase [38], where it bound to the active site and directly competed with the substrate from interacting with α-glucosidase. These results are in line with some previous studies [23,39], in which POC inhibited α-glucosidase in a competitive manner.…”
Section: Resultsmentioning
confidence: 74%